Successful Resuscitation in a Model of Asphyxia and Hemorrhage to Test Different Volume Resuscitation Strategies. A Study in Newborn Piglets After Transition - Mendler, Marc R.; Schwarz, Stephan; Hechenrieder, Lisbeth; Kurth, Steven; Weber, Birte; Höfler, Severin; Kalbitz, Miriam; Mayer, Benjamin; Hummler, Helmut D. (Frontiers in Pediatrics, 2018)
Background: Evidence for recommendations on the use of volume expansion during cardiopulmonary resuscitation in newborn infants is limited. Objectives: To develop a newborn piglet model with asphyxia, hemorrhage and cardiac arrest to test different volume resuscitation on return of spontaneous circulation (ROSC). We hypothesized that immediate red cell transfusion reduces time to ROSC as compared to the use of an isotonic crystalloid fluid. Methods: Forty-four anaesthetized and intubated newborn piglets (age 32h (12-44h), weight 1220g (1060-1495g), Median (IQR)) were exposed to hypoxia and blood loss until asystole occurred At this point they were randomized into two groups: 1. Crystalloid group: receiving isotonic sodium chloride (n=22) 2. Early transfusion group: receiving blood transfusion (n=22) In all other ways the piglets were resuscitated according to ILCOR 2015 guidelines (including respiratory support, chest compressions and epinephrine use). One hour after ROSC piglets from the crystalloid group were randomized in two sub-groups: late blood transfusion and infusion of isotonic sodium chloride to investigate the effects of a late transfusion on hemodynamic parameters. Results: All animals achieved ROSC. Comparing the crystalloid to early blood transfusion group blood loss was 30.7ml/kg (22.3–39.6ml/kg) vs. 34.6ml/kg (25.2–44.7ml/kg), Median (IQR). 11 subjects did not receive volume expansion as ROSC occurred rapidly. 33 animals received volume expansion (16 vs. 17 in the crystalloid vs. early transfusion group). 14.1% vs. 10.5% of previously extracted blood volume in the crystalloid vs. early transfusion group was infused before ROSC. There was no significant difference in time to ROSC between groups (crystalloid group: 164s (129–198s), early transfusion group: 163s (162–199s), Median (IQR)) with no difference in epinephrine use. Conclusions: Early blood transfusion compared to crystalloid did not reduce time to ROSC, although our model included only a moderate degree of hemorrhage and ROSC occurred early in 11 subjects before any volume resuscitation occurred.